Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.